Compromising between European and US allergen immunotherapy schools: Discussions from GUIMIT, the Mexican immunotherapy guidelines - Larenas Linnemann, Désirée; Rodríguez Pérez, Noel; Luna Pech, Jorge A.; Rodríguez González, Mónica; Blandón Vijil, María Virginia; Del Río Navarro, Blanca E.; Costa Domínguez, María del Carmen; Navarrete Rodríguez, Elsy Maureen; Macouzet Sánchez, Carlos; Ortega Martell, José Antonio; Pozo Beltrán, César Fireth; Estrada Cardona, Alan; et al. (2020)
Background: Allergen immunotherapy (AIT) has a longstanding history and still remains the only disease-changing treatment for allergic rhinitis and asthma. Over the years 2 different schools have developed their strategies: the United States (US) and the European. Allergen extracts available in these regions are adapted to local practice. In other parts of the world, extracts from both regions and local ones are commercialized, as in Mexico. Here, local experts developed a national AIT guideline (GUIMIT 2019) searching for compromises between both schools. Methods: Using ADAPTE methodology for transculturizing guidelines and AGREE-II for evaluating guideline quality, GUIMIT selected 3 high-quality Main Reference Guidelines (MRGs): the European Academy of Allergy, Asthma and Immunology (EAACI) guideines, the S2k guideline of various German-speaking medical societies (2014), and the US Practice Parameters on Allergen Immunotherapy 2011. We formulated clinical questions and based responses on the fused evidence available in the MRGs, combined with local possibilities, patient's preference, and costs. We came across several issues on which the MRGs disagreed. These are presented here along with arguments of GUIMIT members to resolve them. GUIMIT (for a complete English version, see Supplementary data) concluded the following: Results: Related to the diagnosis of IgE-mediated respiratory allergy, apart from skin prick testing complementary tests (challenges, in vitro testing and molecular such as species-specific allergens) might be useful in selected cases to inform AIT composition. AIT is indicated in allergic rhinitis and suggested in allergic asthma (once controlled) and IgE-mediated atopic dermatitis. Concerning the correct subcutaneous AIT dose for compounding vials according to the US school: dosing tables and formula are given; up to 4 non-related allergens can be mixed, refraining from mixing high with low protease extracts. When using European extracts: the manufacturer's indications should be followed; in multi-allergic patients 2 simultaneous injections can be given (100% consensus); mixing is discouraged. In Mexico only allergoid tablets are available; based on doses used in all sublingual immunotherapy (SLIT) publications referenced in MRGs, GUIMIT suggests a probable effective dose related to subcutaneous immunotherapy (SCIT) might be: 50–200% of the monthly SCIT dose given daily, maximum mixing 4 allergens. Also, a table with practical suggestions on non-evidence-existing issues, developed with a simplified Delphi method, is added. Finally, dissemination and implementation of guidelines is briefly discussed, explaining how we used online tools for this in Mexico. Conclusions: Countries where European and American AIT extracts are available should adjust AIT according to which school is followed.